Assessing the amount of interdental bone in posterior areas of the mandible for placing orthodontic mini-implants. - Nasrin Esfahanizadeh; Damoun Shahraki; Hamidreza Daneshparvar; Ahmad Reza Talaei Pour; Mohammad Ali Saghiri; Ahmad Sheibaninia; Shadab Rashtak (Tehran University of Medical Sciences, 2013)
Objective : The aim of this study was to assess the amount of interdental bone in posterior areas of the mandible for placing orthodontic mini-implants to provide and control anchorage in orthodontic treatment. Materials and Methods : The amount of interdental bone in areas between the second premolars and first molars, first and second molars on the right and left sides of the mandible were determined in fifty patients by RVG using periapical radiographs. The images were assessed using Cygnus Media Software to determine the mesio-distal width of the interdental bone, starting at the crest of the alveolar bone (2 mm below the CEJ) every one millimeter up to 12 mm from the CEJ. The actual amount of interdental bone and the effect of related factors were assessed using chi-square test at a 95% confidence interval. Results : The minimum desired interdental bone width for placing mini-implants, 3 mm from the CEJ, between the second premolar and first molar and the first and second molars of the mandible on both sides were significantly different (p